Les conquérants de l’inutile. Expression et diffusion d’un modèle de masculinité héroïque dans l’alpinisme français d’après-guerre - Delphine Moraldo (Genre, Sexualité et Société)
Mountaineering, traditionally a men’s sport, takes a heroic and warlike connotation during periods of conquest of new mountain ranges. This was the case during the 1950s and 1960s, the so-called golden age of Himalayan climbing, when nations were competing for the first ascents of the fourteen 8000m peaks of the world. In the history of French mountaineering, it was a « particular moment » suitable for studying the processes of expression and diffusion, within the realm of mountaineering, of a hegemonic model of masculinity that I call « heroic ». This is what I will try to show from an analysis of expedition narratives and autobiographies of French mountaineers from the 1950s and 1960s, considered within the historical context within which this model of masculinity appears in France. In order to emphasise the specificity of the French situation, French mountaineering will be compared with British mountaineering of the same time period.